Esterification of Acrylic Acid With 2-Ethyl Hexanol Over Sulfated Ferum Promoted Zirconia - Mohd Aedlan, Nur Ahmad (2012)
Acrylate polymer belongs to a group of polymers which could be generally referred as plastics. 2-ethyl hexyl acrylate, in which when it is polymerized, it becomes an ingredient in paints, coatings, textiles, adhesives, plastics and many other applications. Homogeneous acid commonly used as reaction catalysts are toxic, corrosive and difficult to be removed from the reaction medium while solid catalysts are easier to be removed and recycled from the reaction products. This will make the reaction process longer and reduce the waste production which gives environment and economic value to nature and industry respectively. The research objective is to determine the effectiveness of heterogeneous catalyst, sulfated ferum promoted zirconia (ZFS) in catalyzing esterification of acrylic acid with 2-ethyl hexanol to produce 2- ethyl hexyl acrylate (2EHA). The research needs to determine the maximum reaction condition for 2EHA esterification reaction and catalyst characterization using XRD, TGA and FTIR. Sulfated Ferum Promoted Zirconia shows the presence of tetragonal phase shape from XRD analysis which is a crystal shape and proved that the catalyst produces is ZFS. Thermal stability studies using TPD shows that the catalyst is stable to catalyze the reaction up until 570°C with total decomposition of 11.89 % (1.081mg). FTIR analysis show the presence of component of S=O region which is known as pyrosulfates group and OH group where the reaction conversion depends on the presence of these group. From the reaction analysis, the best reaction condition for esterification of 2-Ethyl Hexyl Acrylate using Sulfated Ferum Promoted Zirconia catalyst is 90ºC for 8 hours with 1:3 acrylic acids to 2 ethyl hexanol molar ratio using 1.5wt% catalyst loading. The reaction conversion from this reaction condition is 77.22%.